Clinical characteristics of non‐convulsive status epilepticus diagnosed by simplified continuous electroencephalogram monitoring at an emergency intensive care unit. Issue 1 (27th May 2016) - Egawa, Satoshi; Hifumi, Toru; Kawakita, Kenya; Manabe, Arisa; Nakashima, Ryuta; Matsumura, Hikari; Okazaki, Tomoya; Hamaya, Hideyuki; Shinohara, Natsuyo; Shishido, Hajime; Takano, Koshiro; Abe, Yuko; et al.
Abstract : Aim: The present study aimed to elucidate the clinical characteristics of non‐convulsive status epilepticus (NCSE) in patients with altered mental status (AMS). Methods: This single‐center retrospective study comprised 149 patients who were hospitalized between March 1, 2015 and September 30, 2015 at the emergency intensive care unit (ICU) of the Kagawa University Hospital (Kagawa, Japan). The primary outcome was NCSE incidence. The secondary outcome was the comparison of duration of ICU stay, hospital stay, and a favorable neurological outcome, as assessed using the modified Rankin Scale score, at discharge from our hospital between patients with and without NCSE. Favorable neurological outcome and poor neurological outcome were defined as modified Rankin Scale scores of 0–2 and 3–6, respectively. Results: Simplified continuous electroencephalogram was used to monitor 36 patients (median age, 68 years; 69.4% males) with acute AMS; among them, NCSE was observed in 11 (30.1%) patients. Rates of favorable neurological outcome, duration of ICU stay, and hospital stay were not significantly different between the NCSE and non‐NCSE groups ( P = 0.45, P = 0.30, and P = 0.26, respectively). Conclusion: Approximately 30% of the patients with AMS admitted to emergency ICUs developed NCSE. The outcomes of AMS patients with and without NCSE did not differ significantly when appropriate medical attention and antiepileptic drugs were initiated. Simplified continuous electroencephalogram monitoring may be recommended in patients with AMS in emergency ICU to obtain early detection of NCSE followed by appropriate intervention.